Antibacterial Activity of Ethanol Extract of Portulaca oleracea L. Herb from Various Extraction Methods Against Salmonella typhimurium - MAULITA CUT NURIA; AULIA EVERESTINA PUJAKA; ERIKA INDAH SAFITRI (Indonesian Society for microbiology, 2021)
Salmonella typhimurium bacteria could cause gastroenteritis and its growth could be controlled by the active compounds from natural products, which is Portulaca oleracea L. herb. Portulaca oleracea contained tannin, saponins and flavonoids compounds which had different characteristics towards temperature extraction. This study aims to determine the antibacterial activity of ethanol extract of the Portulaca oleracea herb from various extraction methods against S. typhimurium bacteria. Extraction of Portulaca oleracea herb was carried out with four variations methods which were the cold method (maceration and percolation) and heat method (soxhlet and refluxs) using 96% ethanol solvent. The four types of extract were tested for their antibacterial activity by disk diffusion at concentrations of 30%, 35%, 40%, 45% and 50% (b/v). The positive control was chloramphenicol 30 Âµg/disk, while the negative control was DMSO solvent. The results of antibacterial activity test in the form of zone of inhibition were statistically analyzed by Two Way Anova. The results showed that the ethanol extract of the Portulaca oleracea herb from various extraction methods had antibacterial activity against S. typhimurium. There was a significantly difference in the antibacterial activity of ethanol extract of the Portulaca oleracea herb obtained from the reflux method with other methods (maceration, percolation and soxhlet) against S. typhimurium. Keywords: ethanol extract of Portulaca oleracea L. herb, antibacterial, Salmonella typhimurium, various extraction methods